Effect of immobilization rate and enzyme crowding on enzyme stability under different conditions. The case of lipase from Thermomyces lanuginosus immobilized on octyl agarose beads. (May 2017) - Zaak, Hadjer; Siar, El-Hocine; Kornecki, Jakub F.; Fernandez-Lopez, Laura; Pedrero, Sara G.; Virgen-Ortíz, Jose J.; Fernandez-Lafuente, Roberto
Graphical abstract: Highlights: TLL is very rapidly immobilized on octyl agarose beads. Apparent TLL stability increases using fully loaded biocatalyst due to diffusion problems. The use of very concentrated TLL solutions during immobilization alters the enzyme stability due to enzyme crowding effect. The effects of enzyme crowding on enzyme stability depend on inactivation conditions. Glycerin and high ionic strength improve TLL-OC stability. Abstract: Lipase from Thermomyces lanuginosus (TLL) was immobilized on octyl agarose (OC). Three different TLL-OC biocatalysts were prepared: one lowly loaded using a low enzyme concentration, one fully loaded using a low enzyme concentrations, and a final one using a large excess of enzyme at a higher concentration. The activities after immobilization increased (180%), although diffusion limitations reduced the hyperactivation of the fully loaded preparations (140%). The stabilities of both preparations using low enzyme concentrations were similar under all studied conditions discounting the diffusional limitations of the biocatalyst. However, the biocatalyst prepared using a large concentration of enzyme was less stable that the other preparations at pH 7.0, more stable at pH 5.0 and with a similar stability at pH 9.0. Adding 3 M NaCl, the stability of the fully loaded preparations significantly increased; while the lowly loaded preparation slightly improved enzyme stability. This produced that the biocatalyst prepared under using high enzyme concentration become significantly more stable than the other two TLL preparations. Glycerin increased immobilized TLL stability, in this case all OC-TLL preparations became with similar stabilities. Results show that the TLL concentration during immobilization may greatly affect TLL properties, perhaps due to altering enzyme packing.